Magmatic Response to Subduction Initiation: Part 1. Fore‐arc Basalts of the Izu‐Bonin Arc From IODP Expedition 352. (16th January 2019) - Shervais, John W.; Reagan, Mark; Haugen, Emily; Almeev, Renat R.; Pearce, Julian A.; Prytulak, Julie; Ryan, Jeffrey G.; Whattam, Scott A.; Godard, Marguerite; Chapman, Timothy; Li, Hongyan; Kurz, Walter; et al.
Abstract: The Izu‐Bonin‐Mariana (IBM) fore arc preserves igneous rock assemblages that formed during subduction initiation circa 52 Ma. International Ocean Discovery Program (IODP) Expedition 352 cored four sites in the fore arc near the Ogasawara Plateau in order to document the magmatic response to subduction initiation and the physical, petrologic, and chemical stratigraphy of a nascent subduction zone. Two of these sites (U1440 and U1441) are underlain by fore‐arc basalt (FAB). FABs have mid‐ocean ridge basalt (MORB)‐like compositions, however, FAB are consistently lower in the high‐field strength elements (TiO2, P2 O5, Zr) and Ni compared to MORB, with Na2 O at the low end of the MORB field and FeO* at the high end. Almost all FABs are light rare earth element depleted, with low total REE, and have low ratios of highly incompatible to less incompatible elements (Ti/V, Zr/Y, Ce/Yb, and Zr/Sm) relative to MORB. Chemostratigraphic trends in Hole U1440B are consistent with the uppermost lavas forming off axis, whereas the lower lavas formed beneath a spreading center axis. Axial magma of U1440B becomes more fractionated upsection; overlying off‐axis magmas return to more primitive compositions. Melt models require a two‐stage process, with early garnet field melts extracted prior to later spinel field melts, with up to 23% melting to form the most depleted compositions. Mantle equilibration temperatures are higher than normal MORB (1, 400 °C–1, 480 °C) at relatively low pressures (1–2 GPa), which may reflect an influence of the Manus plume during subduction initiation. Our data support previous models of FAB origin by decompression melting but imply a source more depleted than normal MORB source mantle. Plain Language Summary: This projects looks at how subduction zones form and evolve before island arc volcanism becomes established. Subduction zones are important because they are the primary sites for recycling chemically enriched crustal materials and because they form some of Earth's most important ore deposits. We drilled two deep core holes on the inner trench wall of the Izu‐Bonin subduction zone to recover samples from its earliest history, before formation of Izu‐Bonin island arc volcanoes. Samples from these cores were analyzed chemically to establish how lava compositions varied through time and to understand the processes that control their chemistry. We found a diverse set of lavas, with chemical compositions that are low in elements that are normally enriched in arc lavas. Calculations also show that these lavas were hotter than normal mid‐ocean ridge lavas. We found that the first lavas in a new subduction zone form by the upwelling of hot material from deeper in the Earth, which partially melts as it rises toward the surface. Small amounts of melt formed in equilibrium with garnet deeper in the Earth, while later melts formed in equilibrium with spinel at shallower depths in the Earth. The high extent of melting required, and the high calculated temperatures of these lavas, suggests the involvement of the Manus hot spot, which was located above the newly formed subduction zone some 52 million years ago. The lavas found in these drill holes are similar to lavas found in ocean crust that has been emplaced into mountain belts throughout the world and supports the proposition that in most areas, on‐land ocean crust formed above subduction zones, not at mid‐ocean ridges. Key Points: Fore‐arc basalts (FABs) formed by decompression melting in response to subduction initiation and differ from mid‐ocean ridge basalts FABs form by two‐stage melting, with early garnet field melts extracted prior to spinel field melting, resulting in LREE/HREE depletion Highly depleted FAB may reflect both an older depletion event and higher ambient temperatures related to the Manus plume